Timing synchronization method for pilot‐based coherent detection. (21st October 2015) - Torres, J.; Hernández, F.; Hajj Shehadeh, Y. El
Summary: Cognitive radio systems play an important role in the current digital communication systems. With regard to the methods developed, the importance of a coherent detector with matched filters arises, taking into account the optimal properties verified in detection and sensing time. However, the need of perfect timing limits the applicability of this type of system, because of the complexity in hardware implementation. Based upon slope estimation techniques, the present article addresses new methods for tackling this problem. A low complexity system is obtained, and applications can be considered for finding white space in digital television. The results show a good performance with regard to the probability of detection and robustness regarding frequency offset. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Cognitive radio systems play an important role in current digital communication systems. With regard to the methods developed, the importance of a coherent detector with matched filters arises, taking into account the optimal properties verified in detection and sensing time. In this regard, the present article addresses new methods for spectrum‐sensing techniques and exhibits an application for finding white space in digital television.